Potassium and magnesium response of cassava grown in an Ultisol in southern Nigeria - Kang, B.T. (1984)
Results of three consecutive croppings to study the potassium and magnesium responses of two improved cassava cultivars TMS 30395 and 30211 grown on an acid, sandy loam, Ultisol (Typic paleudult) in southern Nigeria is reported. On land newly cleared from Eupatorium fallow a significant potassium response in the first cropping year was observed only with the more vigorous cultivar TMS 30395. Both cultivars responded to potassium applications at rates of 30 and 60 kg Kha−1 in second and third croppings respectively. A significant response to application of 20 kg Mgha−1 was observed in the third crop with cultivar TMS 30211. Cultivar TMS 30395 seems to be more effective in utilizing magnesium from the soil. Potassium and magnesium responses on this Ultisol can be expected when the IN Ammonium Acetate extractable soil K and Mg test levels are ⩽ 0.15 me K 100g−1 and ⩽ 0.20 meMg 100g−1, respectively. Critical tissue concentrations of cassava index leaves sampled at 6 MAP are ⩽ 0.1% K for both cultivars and ⩽ 0.33% Mg for cultivar TMS 30211.